PENINGKATAN HASIL BELAJAR MAPEL PANCASILA MELALUI MEDIA KONKRET SISWA KELAS IV SD AL-ISLAM 2 JAMSAREN TAHUN 2025/2026 - Ayu Kharisma, Naila; Slamet Waluyo, Hanan; Puspita Dewi, Ratih; Sunandar Muttaqin, Shodiq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education plays an important role in shaping students’ character, morals, and attitudes; therefore, its learning process needs to be designed in an engaging, meaningful, and student-centered manner that is appropriate to students’ characteristics. The use of appropriate learning media can help students understand the material more easily, increase their engagement in the learning process, and provide more meaningful learning experiences. This classroom action research aimed to improve students’ learning outcomes in Pancasila Education through the use of concrete media in Class IV B at SD Al-Islam 2 Jamsaren in the 2025/2026 academic year. The research was conducted in response to the problem of low student learning outcomes, with some students not yet achieving the Learning Objective Achievement Criteria (KKTP) in Pancasila Education. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of four cycles. The subjects of the study were 27 students of Class IV B. Data were collected through learning outcome tests administered at the end of each cycle and were analyzed based on the mean scores and percentage of improvement. The results showed a consistent increase in the mean learning outcomes, from 71.44 in the pre-cycle stage to 77.63 in Cycle I, 81.56 in Cycle II, 86.26 in Cycle III, and 92.89 in Cycle IV. Overall, the mean learning outcomes increased by 30.02%. All students also demonstrated gradual improvement in their scores across the cycles. These findings indicate that the use of concrete media is effective in improving students’ learning outcomes in Pancasila Education because it provides direct and meaningful learning experiences and is consistent with the characteristics of elementary school students’ cognitive development at the concrete operational stage.